Integrating Montessori and Contextual Learning to Enhance Early Reading Skills in Fifth-Grade Students with Learning Disabilities - Pagaloran, Nurmiati; Ishartiwi, Ishartiwi (Papanda Publisher, 2025)
Upper elementary students with persistent reading difficulties require specialized interventions beyond conventional instruction. This study investigated the effectiveness of integrating Montessori methods with contextual learning approaches to enhance early reading abilities in fifth-grade students at risk for learning disabilities. A quasi-experimental one-group pretest-posttest design was employed with two fifth-grade male students (aged 10 years) identified with severe reading deficits at SDN 013 Sangatta Selatan, Indonesia. The four-week intervention incorporated Montessori materials (sandpaper letters, movable alphabets, picture-word cards) with contextual connections to students' daily experiences. validated 20-item early reading assessment measuring syllable reading, word recognition, and sentence comprehension was administered pre- and post-intervention. Both participants demonstrated substantial improvements, with mean scores increasing from 27.5% (pretest) to 85% (posttest), representing a 57.5 percentage-point gain. Subject MT improved from 25% to 80% (55% gain), while Subject MA progressed from 30% to 90% (60% gain), both achieving or exceeding the 80% proficiency threshold. Observational data corroborated quantitative findings, showing increased engagement and reduced task avoidance. The Montessori-based contextual approach effectively enhanced early reading abilities in upper elementary students with persistent reading difficulties. The integration of multisensory, concrete materials with real-world contextualization provided accessible pathways to literacy acquisition for students unresponsive to traditional instruction, suggesting promising applications for inclusive literacy education.